Validity and Reliability of Green Skills Instrument (Sains Humanika, 2018)
Green Skills (GS) are the skills based on strong sustainability development from the aspects of technical, value knowledge and attitude that are needed by the workforce in developing economy and environment in the business, industry and society. The objective of this research was to validate the GS instrument. This research adopted the survey research method. Cluster random sampling and simple random sampling methods were utilised in selecting a total of 446 Secondary school students who enrolled the subject of Design all over Peninsular Malaysia. Structural Equation Modelling (SEM) analyses were used to determine validity and reliability in measurement model. Measurement model was fitted the data and was accepted base on suitability index (fit indices), that has been achieved namely CMIN χ2=595.204, with degrees of freedom (df) 132, CMIN/df=4.509 (≤5.0), incremental fit CFI & IFI (≤0.9), and absolute fit RMSEA=0.8(≤0.8). The instrument has been proven to be a good instrument and passed the psychometrics standards. The research findings showed there were a total of 10 elements must be present in the students. The research implicated that GS Model can be used as guidance in cultivating GS in the learning process. This GS Model is expected to cultivate a balanced environment from the aspects of attitude, knowledge and values that are needed in the students. This GS Model also can be used as the basis in developing curriculum as an added-value in training design. Furthermore, it can be used as a module in learning process that gives importance to environmental awareness among students
Keywords: Green skills; sustainability development; environmental awareness; green practice; attitude; knowledge